ON 3-PARAMETER GENERALIZED QUATERNIONS WITH THE LEONARDO p-SEQUENCE - Sacli, Gulsum Yeliz (EDITURA BIBLIOTHECA-BIBLIOTHECA PUBL HOUSE, 2024)
In this article, 3-parameter generalized quaternionic Leonardo -sequence which is a quaternion generalization of the Leonardo -sequence is presented. Several properties are examined by means of their homogeneous and non-homogeneous recursive relations. According to the special cases of 3-parameter lambda(i is an element of{1,2,3,}) and , all the results given in paper are reducible to all quaternions mentioned in this paper
Keywords: Leonardo sequence; recurrence relation; generalized quaternion; FIBONACCI; NUMBERS; Science & Technology - Other Topics